Addressing efficiency interest in architectural technical debt - A measurement and visualization approach for embedded software - Kaufmann, Robert; Odeh, Sam (My University, 2015)
Addressing and managing technical debt is an important part of software development. Unmanaged technical debt, especially architectural technical debt, can lead to additional development overhead and expensive refactoring. However, most research that address architectural technical debt does so by analyzing source code; very little research focus on a more abstract level. The problem with analyzing source code to identify debt is that it is not enough to cover all debt. Similarly, most visualisation of software architecture target lower level artifacts based on static code analysis. Therefore there is a gap in both addressing architectural technical debt and software visualisation on a more abstract level. By utilizing a case study at a company, followed by design research, we contribute to filling this gap by identifying, measuring, and visualizing architectural debt on a higher abstraction level. Specifically, we identify occurring debt items related to efficiency interest and propose methodologies to measure and visualize them utilizing architectural models. Thus, we provide novel techniques of
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology